Results on Interval-Valued Optimization Problems for Vector Variational-Like Inequalities (Journal of Nonlinear Modeling and Analysis, 2025)
The objective of this article is to present a new class of vectorinterval-valued variational-like inequality problems. Based on the concepts ofLU optimal and weakly LU optimal solutions, we derive some relations betweenthe interval-valued programming and variational-like inequality problems. Thestudy of the interplay between interval-valued optimization problems (IVOP)and vector variational-like inequalities (VVLI) combines theoretical advancements under the concept of differentiability and $μ$- invexity. Furthermore,to demonstrate the established linkages, we provide examples and an example demonstrates how well the vector variational inequality problems may beapplied to deal with (MOIVP) problems.
Keywords: Interval-valued programming; invexity; LU-optimal; variational-like inequality problem.